Increased Beat-to-beat Blood Pressure Variability is Associated With Impaired Cognitive Function - Nur Fazidah Asmuje; Sumaiyah Mat; Choon Hian Goh; Phyo Kyaw Myint; Maw Pin Tan (Oxford University Press, 2024)
Indexed by WOS/Scopus/ERA